Herbal Remedies of Wetlands Macrophytes in India - SANTOSH KUMAR; SATYA NARAIN (International Journal of Pharma and Bio Sciences, 2010)
Wetlands provide a unique habitat for several medicinal plants. In spite of their commercial value, the local community utilizes good number of these plants for various curative purposes. A number of these plants are very sensitive to the fluctuation in the normal physic-chemical parameter of the wetland. A slight alteration of the wetland may result in the disappearance or the extinction of these plants. This will ultimately result in large scale economic loss in terms of the medicinal product. Apart from the loss of plants, this will also result in the loss of local knowledge on the medicinal properties of these plants which very often can’t be retrieved. Attempt has been made to document some of the little known medicinal properties of wetland plants used by local community of India.